Religious Factor in Nigerian Politics: Implications for Christian-Muslim Relations in Nigeria - Opeloye, Muhib O. (2014)
Right from the period of struggle against colonization, Nigeria had started to experience two major problems inimical to political stability. These were politicization of ethnicity and politicization of religion. At the initial stage, the problem was more of the former which contributed to the collapse of the First Republic and the start of the Civil War. The demise of the Second Republic as well could not be divorced from ethnic politics. An attempt to put an end to ethnic politics in Nigeria constrained the present military government to approve a two-party system for the Third Republic. Religious politicization had its roots in the pre-independence era, but it started to pose serious problems to the unity of the country only within the last decade. The military government having sensed this problem warned the politicians against the formation of political parties based on religious ideology. It is too early to assess the deterrent value of this warning. However, Nigerians should have been adequately warned of the shape of things to come from the handling of the Shari'a issue under the Third Republic. This paper then shall examine the role religion has played in Nigerian politics and its effects on Christian-Muslim relations.